Design of Large-Scale Prestressing Bucket Foundation for Offshore Wind Turbines - 练继建 丁红岩 张浦阳 于瑞 (Transactions of Tianjin University, 2012)
The key in the force transmission between the tower and the foundation for offshore wind turbines is to transfer the large moment and horizontal loads. The finite element model of a large-scale prestressing bucket founda- tion for offshore wind turbines is set up and the structural characteristics of the arc transition structure of the founda- tion are analyzed for 40--60 channels （20--30 rows） arranged with prestressing steel strand under the same ultimate load and boundary conditions. The mechanical characteristics of the key parts of the foundation structures are illus- trated by the peak of the principal tensile stress, the peak of the principal compressive stress and the distribution areas where the principal tensile stress is larger than 2.00 MPa. It can be concluded that the maximum principal tensile stress of the arc transition decreases with the increasing number of channels, and the amplitude does not change signifi- cantly; the maximum principal compressive stress increases with the increasing number of channels and the amplitude changes significantly; however, for the distribution areas where the principal tensile stress is larger than 2.00 MPa, with different channel numbers, the phenomenon is not obvious. Furthermore, the principal tensile stress at the top of the foundation beams fluctuantly increases with the increasing number of channels and for the top cover of the bucket, the principal tensile stress decreases with the increasing number of channels.